2018
DOI: 10.1111/basr.12152
|View full text |Cite
|
Sign up to set email alerts
|

For Humanistic Management and Against Economics

Abstract: The paper critiques the relationship between personalist ethics and institutional economics, and accepts that institutional economics can be difficult to reconcile with humanistic management that builds on personalist ethics. Even so the paper connects impersonalist ethics with institutional economics. On this ground, the paper demonstrates how theory and practice of personalist humanist management can lean on impersonalist ethics, i.e., institutional economics. Three pathways are laid out for such leanings. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 95 publications
(231 reference statements)
0
1
0
Order By: Relevance
“…Questionnaire surveys have shown that, in some colleges, only 25% of the respondents are satisfied with the role of KPI appraisal in enhancing the professional capacity of teachers. The KPI appraisal goals cannot be realized, mainly due to the poor communication between the implementation department and the faculty [22].…”
Section: Fig 2 Problems In Teachers' Kpi Appraisalmentioning
confidence: 99%
“…Questionnaire surveys have shown that, in some colleges, only 25% of the respondents are satisfied with the role of KPI appraisal in enhancing the professional capacity of teachers. The KPI appraisal goals cannot be realized, mainly due to the poor communication between the implementation department and the faculty [22].…”
Section: Fig 2 Problems In Teachers' Kpi Appraisalmentioning
confidence: 99%